Analysis of XRD stress measurement data of naturally grown oxide films Al2O3 and Cr2O3 based on existing Reuss, Voigt, and Hill models - SARIOĞLU, CEVAT (MANEY PUBLISHING, 2002)
The resistance of naturally grown alumina (Al2O3) and chromia (Cr2O3) scales to cracking and spalling under influence of growth and thermal stresses is a critical aspect of the environmental resistance of high temperature alloys such as Fe and Ni based alloys. The driving force for scale failure is the residual stress developed in the scale. In this study, strain and stress measurement techniques by XRD were reviewed. XRD data for Al2O3 and Cr2O3 films were analysed and discussed with respect to existing models. It was experimentally found that the Reuss model provided the best description of the measured strain data for these films. Strain and stress states of Al2O3 and Cr2O3 films here determined. (C) 2002 IoM Communications Ltd.
Keywords: RESIDUAL-STRESS